2016
DOI: 10.1039/c6ta06634h
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Dacron cloth supported Cu(OH)2 nanobelt arrays for wearable supercapacitors

Abstract: Commercial Dacron cloth is directly used as a substrate for the growth of Cu(OH)2 nanobelt arrays for application in flexible all-solid-state supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 41 publications
5
50
0
Order By: Relevance
“…Figure a presents CV curves of the electrodes with different lattice structures within a potential window of 0–0.5 V (vs Hg/HgO) at 200 mV s −1 in 6 m KOH aqueous electrolyte. It can be clearly observed that each CV curve displays an indistinct anodic peak and a broad cathodic peak, which are quite different from the ideal rectangular CV curves of traditional electrochemical double‐layer capacitors, revealing a typical pseudocapacitance behavior governed by Faradaic reactions 11a. And these CV curves are very similar to the profiles of previously reported Cu(OH) 2 electrodes 11b,19.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Figure a presents CV curves of the electrodes with different lattice structures within a potential window of 0–0.5 V (vs Hg/HgO) at 200 mV s −1 in 6 m KOH aqueous electrolyte. It can be clearly observed that each CV curve displays an indistinct anodic peak and a broad cathodic peak, which are quite different from the ideal rectangular CV curves of traditional electrochemical double‐layer capacitors, revealing a typical pseudocapacitance behavior governed by Faradaic reactions 11a. And these CV curves are very similar to the profiles of previously reported Cu(OH) 2 electrodes 11b,19.…”
Section: Resultssupporting
confidence: 72%
“…As depicted in Figure b, XPS pattern of the electro‐oxidized sample for the Cu 2p core level shows two obvious peaks at 933.7 and 953.5 eV, corresponding to a spin–orbit couple of Cu 2p 3/2 and Cu 2p 1/2 . These two distinct peaks together with their shake‐up satellites at 961.6, 942.8, and 940.5 eV are ascribed to the characteristic peaks of d9 Cu 2+ compounds,11b revealing that a certain amount of electroless plated Cu metal has been successfully oxidized into Cu 2+ . These findings are also in reasonable agreement with previous reports 11a.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The anodic peaks are not obvious due to the fact that transition between the Cu + and Cu 2+ are not intact . The cathodic peaks are 0.49, 0.48, 0.47, 0.46, 0.45, 0.44 and 0.38 V at the scan rates of 2, 5, 7, 10, 15, 20 and 50 mV s −1 , respectively, elucidating that the reversibility is lost with the increasing of scan rates, due to the polarization arose from the charge transfer of the electrode …”
Section: Resultsmentioning
confidence: 99%